Defense Expenditures and Income Inequality: Evidence from Chosen Euro Using Countries - Çenberci, Engin (Muş Alparslan Üniversitesi, 2019)
This paper, aims to find thecointegration and the causality between income inequality and defenseexpenditures in fifteen European Union member countries that used euro currencybefore, during and after the global economic crises in the period of 2005-2016.Applying cointegration and causality tests to the panel data, the paper aims tofill the gap about income inequality and defense expenditures relation in theliterature.

Bu çalışma, 2005-2016 döneminde küresel ekonomik kriz öncesinde, sırasında ve sonrasında avro kullanan on beş Avrupa Birliği üyesi ülkedekigelir eşitsizliği ve savunma harcamaları arasındaki eş bütünleşme ve nedenselliğibulmayı amaçlamaktadır. Panel verisine eş bütünleşme ve nedensellik testleriuygulanarak gelir eşitsizliği ve savunma harcamaları ilişkisine dair  literatürdeki eksikliğin doldurulmasıamaçlanmıştır.
Savunma Harcamaları ve Gelir Eşitsizliği: Seçilmiş Avro Kullanıcısı Ülkelerden Kanıtlar
anemon
Keywords: panel data analysis; defense expenditures; income inequality; panel veri analizi; savunma harcamaları; gelir eşitsizliği